Estimation of Breeding Values from a F2 Progeny Trial and Recurrent Selection of Genotypes in Eucalyptus Tereticornis Smith for F3 Generation Breeding Program - Sircar, Sumita; Sindhu Veerendra, H. C. (Indian Forester, 2010)
A Eucalyptus tereticornis F2 generation progeny trial was established at Midnapore, West Bengal for recurrent selection for fast growth from 49 families. The parents were selected from seedling seed orchards and seedling seed production areas in Karnataka, Tamil Nadu and Pondicherry. The progenies exhibited a good amount of population variation in the form of CV and ANOVA revealed intra- specific variation in all growth components indicating canalization of growth factors from parents and sufficient diversity within the population which can be exploited for further improvement (total height- p = 0.003 and girth at collar- p = 0.001). General combining ability and breeding values obtained from best linear unprediction were estimated for total height and girth at collar. The growth components showed wide ranges in these parameters suggesting a good interaction between alleles. A recurrent selection was made with ten best parents having highest breeding for synthesizing F3 generationbreeding population.